Persepsi Masyarakat Tentang Radikalisme Agama (Studi di Kecamatan Mpunda Kota Bima) - Nurmawadah Rahmah; Muh. Zubair; Bagdawansyah Alqadri (LP2M STIT Palapa Nusantara, 2022)
This study aims to determine the public's perception of religious radicalism and the role of religious leaders in anticipating religious radicalism in Mpunda District, Bima City. This study uses a qualitative approach with the type of research is descriptive. This research was conducted in Mpunda District, Bima City for one month, the subjects of this research were the people in Mpunda District, Bima City, and the research informants were government officials, community leaders, and religious leaders. Data collection techniques used in this study were observation, structured interviews, and documentation. To analyze the data using 3 methods according to Miles and Huberman, including data reduction (Data Reduction), data presentation (Data Display), Verification/Conclusion Drawing. The results showed that people's perceptions of religious radicalism: (1) Religious radicalism arises because of a lack of understanding of religion, (2) The view that only Islam adheres to radical movements is wrong because radicalism can potentially be carried out by all religions. The role of religious leaders in anticipating religious radicalism is to provide counseling to the public about the dangers of radicalism.